Original paperSatisfaction with life in a group of psoriasis patients - Jankowiak, Barbara; Sekmistrz, Sylwia; Kowalewska, Beata; Niczyporuk, Wiaczesław; Krajewska-Kułak, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Psoriasis is one of the most frequent inflammatory diseases of the skin, associated with an epidermal proliferation and a specific morphology of lesions. Patients with psoriasis perceive their appearance specifically; they are frequently rejected by their surroundings and perceive their quality of life as considerably poorer. Aim: To evaluate the satisfaction with life in patients with psoriasis, and to analyze the effect of this disease on the prevalence of depression in this group. Material and methods: The study included 100 psoriasis vulgaris patients treated at the Voivodeship Outpatient Clinic of Skin and Venereal Diseases in Lomza (Poland). Sociodemographic data of the participants and the clinical characteristics of the disease were collected using a standardized questionnaire survey. The global feeling of satisfaction with life was evaluated with the Satisfaction with Life Scale and the Beck’s Depression Inventory. Results: Mean SWLS scores suggested that the examined patients experienced moderate levels of satisfaction with life (18.92 and 18.69 points in women and men, respectively). The life satisfaction was the highest amongst patients between 50 and 60 years of age (p = 0.81). The mean score of the Beck Depression Inventory was at a threshold of mild depression (14.08 and 13.65 points in women and men, respectively). Conclusions : Our participants presented moderate levels of satisfaction with life. A lower satisfaction with life was associated with a poorer quality of life and a higher prevalence of depressive symptoms.